The Impact of Dedicated Cardiac Intensive Care Units on Outcomes in Pediatric Cardiac Surgery: A Virtual Pediatric Systems Database Analysis - Bagdure, Dayanand N.; Custer, Jason W.; Foster, Cortney B.; Blackwelder, William C.; Mishcherkin, Vladimir; Portenoy, Allison; Bhutta, Adnan (Journal of Pediatric Intensive Care, 2020)
Care of children undergoing cardiac surgery occurs in dedicated cardiac intensive care units (CICU) or mixed intensive care units. In this article, we analyzed data from Virtual Pediatric Systems (VPS, LLC) database (2009–2014) for children < 18 years of age undergoing cardiac surgery, classified according to Society of Thoracic Surgery–European Association of Cardiothoracic Surgery (STS-EACTS) risk category. We had 25,052 (52%) patients in 53 mixed units (mortality rate, 2.99%), and 22,762 (48%) patients in 19 dedicated CICUs (mortality rate, 2.62%). There was a direct relationship between STS-EACTS risk category and death rate in both units. By multivariable logistic and linear regression, there was no difference in mortality between mixed unit and CICU death rates within STS-EACTS risk categories. We found no difference in outcomes for children undergoing cardiac surgery based on the unit type (dedicated CICU or mixed unit).
Keywords: pediatrics; outcomes; cardiac surgery